2022
DOI: 10.1002/eap.2739
|View full text |Cite
|
Sign up to set email alerts
|

Leaf litter decomposition and its drivers differ between an invasive and a native plant: Management implications

Abstract: Litter decomposition is a key process of the carbon cycle in terrestrial and aquatic ecosystems. The dominant conceptual model of litter decomposition assumes that environmental conditions, litter traits, and decomposer composition control litter decomposition in a decreasing order, yet whether this hierarchical model applies to both invasive and native plant species is unknown. Here, by comparing a widespread invasive plant and its native counterpart in Chinese coastal saltmarshes, we aimed to examine whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In addition to the traditional impacts, such as competition, predation, and disease transmission, IAS can also influence key ecological processes during their invasions. For example, Cheng et al (2023) conducted field surveys across a wide 18° latitudinal range and a 90‐day incubation experiment. They found that variations existed in leaf litter decomposition and its dominant controlling factors between native and invaded plant communities.…”
Section: Impact and Control Of Invasive Speciesmentioning
confidence: 99%
“…In addition to the traditional impacts, such as competition, predation, and disease transmission, IAS can also influence key ecological processes during their invasions. For example, Cheng et al (2023) conducted field surveys across a wide 18° latitudinal range and a 90‐day incubation experiment. They found that variations existed in leaf litter decomposition and its dominant controlling factors between native and invaded plant communities.…”
Section: Impact and Control Of Invasive Speciesmentioning
confidence: 99%
“…S. alterniflora has reduced biodiversity in China's coast by displacing native salt marsh plants, encroaching into mangrove gaps, and transforming mudflat habitats into salt marshes (Li et al, 2022; Zhang et al, 2012). S. alterniflora has homogenized soil communities (Zhang et al, 2019), has a higher leaf litter decomposition rate than the native Phragmites australis across a range of latitude (Cheng et al, 2022), and has driven losses in habitat and food resources of migratory birds (Gan et al, 2010). Its spread has destroyed aquaculture industries that were based on farming mudflat species such as razor clams.…”
Section: Figurementioning
confidence: 99%
“…We here used an experimental system in a saltmarsh plant community to investigate the effect of genotypic diversity of a foundation native species Scirpus mariqueter Tang & Wang on the growth of Spartina alterniflora Loisel., an aggressive perennial grass that has invaded saltmarshes globally (Cheng et al, 2024). The native S. mariqueter is a perennial sedge that is endemic to China and is mainly distributed in saltmarshes of the Yangtze River estuary and Hangzhou Bay (Sun et al, 2001), but has experienced severe population decline and loss of genetic diversity because of land-use change and invasion by S. alterniflora (Ma et al, 2009).…”
mentioning
confidence: 99%